CO-EXISTENCE OF UNDER AND OVER-NUTRITION AMIDST THE COVID-19 PANDEMIC - Lestari Octavia; Iskari Ngadiarti (PERSATUAN AHLI GIZI INDONESIA, 2022)
COVID-19 pandemic resulted in the prevalence of under, and over-nutrition increased. As a representative of undernutrition, stunting has become a severe public problem. Stunting was a manifestation of chronic malnutrition found in under-five-year-old children. The short stature of the children would hamper growth and development and might affect the disease progression in the future. Not only stunting but also obesity has also become a new issue in low-middle income countries (LMICs). The shift of urbanization heightened the prevalence of obesity in LMICs. This narrative review highlighted the increment of malnutrition in LMICs based on the literature findings during the COVID-19 pandemic and some possible factors related to the outcome. The articles for this review were obtained from verified international journal articles in the National Centre for Biotechnology Information (NCBI)/PubMed and Cochrane Library website. Eleven papers were collected to address malnutrition during the pandemic. Some related factors are: socioeconomic, dietary intake, sanitation and hygiene, health facility, and self-isolation contributed to the double malnutrition problem. Therefore, it is mandatory to suggest the appropriate approach to mitigate malnutrition in children by enriching nutrition education and knowledge programs to assist in resolving the public health problem.